Human resource management system with human relations perspective in the industrial revolution 4.0 era in high schools - Anongsack Mahavong (Universitas Lampung, 2022)
It is widely accepted that human existence has now changed dramatically as a result of the Fourth Industrial Revolution in terms of thinking, living, and interacting. The fast advancement of technology has had a significant impact on this transition. Equally significant is the impact of the Fourth Industrial Revolution on education. To be able to synergize with the world's rapid growth, education, the engine of cultural change and progress, must be responsive to the onset of this era. Human resource management is the most important factor in enhancing the quality of education so it can adapt to rapidly-changing circumstances in order to deal with this type of change. Human resource management can benefit from an understanding of human relations. This method is effective for humanizing employees in organizations, allowing them to work safely, cheerfully, and with a sense of fulfilment because they are respected. High school education is intended to prepare students to manage human resources effectively. Human connections should prepare high school students for the fourth industrial revolution.